2022
DOI: 10.1124/jpet.121.001071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Glycine Transporter-1 Inhibitor Iclepertin (BI 425809) on Sensory Processing, Neural Network Function, and Cognition in Animal Models Related to Schizophrenia

Abstract: N-methyl-D-aspartate (NMDA) receptor hypofunction leading to neural network dysfunction is thought to play an important role in the pathophysiology of cognitive impairment associated with schizophrenia (CIAS). Increasing extracellular concentrations of the NMDA receptor co-agonist glycine through inhibition of glycine transporter-1 (GlyT1) has the potential to treat CIAS by improving cortical network function through enhanced glutamatergic signaling. Indeed, the novel GlyT1 inhibitor iclepertin (BI 425809) imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In order to validate the in vivo effect of glycine in promoting tumor growth and vasculogenesis, we tested the effect of a selective and orally active glycine transporter 1 (GlyT1) inhibitor [ 48 50 ]. It has been demonstrated that GlyT1 inhibitor is able to increase the plasma and cerebrospinal fluid glycine concentration in rats and humans [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to validate the in vivo effect of glycine in promoting tumor growth and vasculogenesis, we tested the effect of a selective and orally active glycine transporter 1 (GlyT1) inhibitor [ 48 50 ]. It has been demonstrated that GlyT1 inhibitor is able to increase the plasma and cerebrospinal fluid glycine concentration in rats and humans [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds for which drug developers have followed this strategy have yielded promising results on electrophysiological measures as well as indices of social and cognitive functioning in patients and animal models. For instance, drugs increasing the synaptic concentration of the NMDAr co-agonists glycine and D-serine or acting on other aspects of the glutamatergic synapse are showing promising results on EEG and behavioral measures in preclinical and clinical trials for social and cognitive symptoms of SZ [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Iclepertin (BI 425809) is a GlyT-1 inhibitor developed by Boehringer Ingelheim specifically for the treatment of cognitive impairment accompanying schizophrenia. In preclinical trials, 104 iclepertin alleviated MK-801-induced deficits in EEG biomarkers related to cognitive functioning such as N1 amplitude and N1 gating. Moreover, it enhanced disrupted working and episodic memory in behavioral tasks in rodents.…”
Section: Taar1 As a Novel Pharmacotherapeutic Target In The Therapy O...mentioning
confidence: 99%